Carriers of values in axiological education of children in postmodern epoch - Langier, Cecylia; Лангер, Цецилія (My University, 2016)
The essential challenge of today’s education of young generation is introducing young people to the world of values so that, they can understand it, accept and adopt it as their own. It is extremely difficult task because young generation is exposed to influence of many adverse phenomena, which can pose a risk for proper personality formation. Therefore very important role in process of education is played by carriers of values, which are source of learning and understanding of basis axiological categories. This article presents issue of children’s education in values. In particular it emphasizes role of particular educational environments that practice preferred hierarchy of values in everyday life, which is a foundation of child’s personality development. Special attention is given to the role of carriers of values in this process, which stimulate emotions and introduce young person in basic axiological categories. У статті наголошується, що суттєвою проблемою сучасного виховання молодого покоління є його імплементація у світ цінностей, на засадах прийняття останніх як власних. Це завдання є надзвичайно складним, оскільки молоде покоління піддається впливу багатьох несприятливих чинників, що становлять небезпеку для формування особистості. Тому непересічну роль у процесі виховання відіграють носії цінностей, котрі є джерелом знань і розуміння основних аксіологічних категорій. Автор інтерпретує проблему виховання дітей у контексті цінностей. Зокрема, підкреслює роль конкретних освітніх середовищ, які фіксують переважаючу ієрархію цінностей в повсякденному житті, що є основою розвитку особистості дитини. Особлива увага приділяється ролі носіїв цінностей в цьому процесі, які стимулюють емоції і визнання молодої людини в основних категоріях аксіології.
Carriers of values in axiological education of children in postmodern epoch
Keywords: child; value; education; дитина; цінності; виховання; культура; постмодернізм